О возможности использования украинских фамилий для оценки уровня инбридинга - Атраментова, Л.А.; Горпинченко, М.Ю. (Фактори експериментальної еволюції організмів, 2014)
Aims. To investigate the possibility of using Ukrainian surnames to estimate inbreeding in the population of Ukraine. Methods. 30320 persons were analysed in Valkovsky area (4154 surnames) and 7930 persons in Kolomak area (1084 surnames). Calculation of random inbreeding for each community was conducted over the frequencies of surnames in its population using Crow & Mange method. Results. The level of inbreeding was calculated from the data on the distribution of the surnames in the Valkovsky and Kolomak district; it varies (0.49–14.35)×10⁻³. Spearman correlation coefficient between the level of inbreeding and the number of inhabitants in Valkovsky area reaches -0.788, in Kolomak area reaches -0.891. Pearson correlation coefficient between the level of inbreeding and the number of inhabitants reaches -0.684 in the Valkovsky area and reaches -0.795 in Kolomak area. Conclusions. Ukrainian surnames can be used as a marker for quasigenetic study of population structure. In the studied areas between the level of inbreeding and the number of inhabitants we registered a strong feedback.